(untitled) - Kingsbury, Noël (London, Great Britain, 1996)
Breaking new ground with the first comprehensive guide to achieving stunning visual effects with architectural plants, this innovative book showcases the most attractive of these plants and explains how any garden can be transformed with some simple planting tricks. From stunning topiary to spiky succulents, this is the most complete guide to all aspects of planting and designing with architectural plants. Photos, 100 in color
Keywords: Landscape plants,Landscape plants; Pictorial works